Morpho-physiological trait variability in oilseed brassica (Brassica juncea L) germplasms under rainfed climates: Morpho-physiological trait variability in oilseed brassica (Brassica juncea L) germplasms under rainfed climates - V V SINGH; L P SHARMA; BALBEER; B RAM; R S JAT; H K SHARMA; PRIYAMEDHA; H S MEENA; M L MEENA; P K RAI (Journal of Oilseeds Research, 2023)
One hundred and forty-seven advance progenies of oilseed brassica germplasms along with three check varieties were evaluated in an augmented block design with seven blocks. Observations were recorded on fourteen morpho-physiological characters. Analysis of variance revealed that the mean squares due to progenies were significant for all the characters under study except number of primary branches/plant, seeds/silique and siliquae length. Heritability estimates were high (50%) for most of the characters. High heritability along with high genetic advance was found for siliquae/plant, biological yield/plant and seed yield/plant. Progenies, BPR-1733-72-2, BPR-1743-98-1, BPR-1686-34-11, BPR-1758-12-56, BPR-1733--71-1, BPR-1758-7-49, BPR-1758-30-64, BPR-1743-92-1, BPR-1733-38-1, and BPR-1758-11-52 were selected on the basis of significant superiority in terms of seed yield/plant over the best check RH 406. The best progenies may further be used in hybridization programme as parents to develop high yielding varieties for rainfed conditions.